Performance Evaluation of a Prototype Rotary Dryer for Granulated Palm Sugar Drying - Gilang Ramdani; Agus Sutejo; Wawan Hermawan; Annastasha Diandra Putri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Granulated palm sugar requires efficient drying to meet industrial quality standards and accelerate production. This study aimed to evaluate the performance of a prototype rotary dryer in reducing moisture content to a maximum target of 2.5%. Tests were conducted at rotation speeds of 23.83±0.1 RPM and 41.83±0.1 RPM with drying durations of 1, 2, and 3 h using a 500-g batch capacity. All treatments were performed in triplicates, and successfully reduced moisture below the 2.5% target, meeting SNI 01-3743-2021 and the company’s internal standards. The optimal condition, determined using the Simple Additive Weighting (SAW) method, was 23.8±0.1 RPM for 1 h, resulting in a final moisture of 2.4%, a product loss of 14.4%, and the lowest energy cost of IDR 821. Higher rotation speed increased the product loss to 55.07% due to centrifugal forces and uneven heat distribution. Sugar adhering to the cylinder walls highlighted the need for improved fin design and airflow. Future development should incorporate stable heating, expanded rotation speed (15–50 RPM) and temperature (60–80°C) variations, and automatic controls for small- to medium-scale food industry applications.